Pelatihan Pembuatan Platform Ajar Online Terintegrasi Game Edukatif untuk Mendukung Implementasi Kurikulum Merdeka - Asra, Surya; Rahmiati, Rahmiati; Chairuddin, Chairuddin; Isda, Irma Dewi; Fadhila, Syairah (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Many teachers are not ready to fulfill all the demands contained in the Independent Curriculum (Kurikulum Merdeka). In the field, the teachers experience challenges in creating interactive hybrid learning. One of the challenges is the use of the Internet of Things in creating teaching platforms and integrating online educational games into every learning meeting. Therefore, this community service activity aims at providing an assistance on how to create an online teaching platform integrated educational games. The method used in this activity was an adopted combination method including lecturing, discussions, demonstrations, exercises/practice, working instructions, and simulations. This activity was attended by 21 junior high school teachers consisting of various fields of study. This activity succeeded in making every teacher who took part in this activity have a teaching platform on a Padlet account according to their field of study and integrated with Quizizz game. Besides, this training also changed teachers’ perception. They found the integrated platform is easier to create after receiving training. In addition, they were also motivated to apply hybrid learning to support the implementation of the independent curriculum.